Cardioprotective Activity of N′′,N′′′-Bis[5-methyl-2-oxo-1,2-dihydro-3H-indol-3-ylidene]carbonohydrazide Derivative against Doxorubicin Induced Cardiotoxicity in Rats - Salma Tabassum; Kiran Gangarapu; Gouthami Thumma; Sarangapani Manda; Rama Narsimha Reddy Anreddy (Journal of Chemistry)
The present study was aimed at evaluating the cardioprotective effect of novel synthetic N′′,N′′′-bis[5-methyl-2-oxo-1,2-dihydro-3H-indol-3-ylidene]carbonohydrazide derivative, by estimating the various biomarkers like creatine kinase-myoglobin (CK-MB), lactate dehydrogenase (LDH), aspartate aminotransferase (AST), and triglycerides (TG) in plasma and antioxidants like catalase, superoxide dismutase in heart tissue homogenate, and histopathological examination of heart tissues. The results showed the significant (P<0.05) dose dependent decrease in elevated cardiotoxic biomarkers CK-MB, LDH, AST, and TG levels. The histopathological studies of heart tissues showed mild degeneration of muscle bundles and less interstitial edematous changes. The results showed the significant (P<0.05) dose dependent increase in antioxidant enzymes catalase and superoxide dismutase in heart tissue homogenates. These observations enable us to conclude that N′′,N′′′-bis[5-methyl-2-oxo-1,2-dihydro-3H-indol-3-ylidene]carbonohydrazide has cardioprotective activity against doxorubicin induced cardiotoxicity.